Development of a Novel Cocktail Enzyme-Linked Immunosorbent Assay and a Field-Applicable Lateral-Flow Rapid Test for Diagnosis of Contagious Bovine Pleuropneumonia - Heller, Martin; Gicheru, Nimmo; Tjipura-Zaire, Georgina; Muriuki, Cecilia; Yu, Mingyan; Botelho, Ana; Naessens, Jan; Jores, Joerg; Liljander, Anne M. (American Society for Microbiology, 2016)
Contagious bovine pleuropneumonia (CBPP) is a severe respiratory disease that is widespread in sub-Saharan Africa. It is caused by Mycoplasma mycoides subsp. mycoides , a bacterium belonging to the Mycoplasma mycoides cluster. In the absence of an efficient CBPP vaccine, improved and easy-to-use diagnostic assays for recurrent testing combined with isolation and treatment of positive animals represent an option for CBPP control in Africa. Here we describe the comprehensive screening of 17 immunogenic Mycoplasma mycoides subsp. mycoides proteins using well-characterized bovine sera for the development of a novel cocktail enzyme-linked immunosorbent assay (ELISA) for laboratory use. Two recombinant Mycoplasma immunogens, MSC_0136 and MSC_0636, were used to set up a standardized cocktail ELISA protocol. According to the results from more than 100 serum samples tested, the sensitivity and specificity of the novel cocktail ELISA were 85.6% and 96.4%, respectively, with an overall diagnostic accuracy comparable to that of the Office International des Epizooties (OIE)-prescribed serological assays. In addition, we provide a proof of principle for a field-applicable, easy-to-use commercially produced prototype lateral-flow test for rapid (<30-min) diagnosis of CBPP.